Coronaphobia in patients with fibromyalgia - Sevinç Külekçioğlu,; Merve Akyüz,; Özenç İnan,; Alp Çetin, (Archives of Rheumatology, 2022)
Objectives: This study aims to evaluate the level of coronaphobia caused by the novel coronavirus disease 2019 (COVID-19) pandemic in patients with fibromyalgia syndrome (FMS) and to compare the results in patients without FMS. Patients and methods: Between August 2020 and October 2020, a total of 61 patients who were admitted to our outpatient clinic were included. The patients were divided into two groups as Group 1 (n=30; 2 males, 28 females; mean age: 43.2±9.3 years; range, 21 to 61 years) consisting of patients who were newly diagnosed or under follow-up for FMS and Group 2, the control group, (n=31; 4 males, 27 females; mean age: 49±10.7 years; range, 25 to 66 years) consisting patients who presented with any locomotor system complaint and were not diagnosed with FMS. Sociodemographic data of the patients and comorbidities were recorded. All the patients in both groups completed the COVID-19 Phobia Scale (C19P-S). Results: The C19P-S total score and psychological, psychosomatic, social, and economic subscale scores were statistically significantly higher in the FMS group than the control group (p<0.05). Conclusion: Our study results suggest that FMS patients have more concerns in this extraordinary global pandemic situation. Early detection of coronaphobia and timely psychological support are critical for individuals prone to psychological disorders, such as FMS.